Efficient antibacterial AIEgens induced ROS for selective photodynamic treatment of bacterial keratitis - Cai, Wenting; Shen, Tianyi; Wang, Dong; Li, Tingting; Yu, Jing; Peng, Chen; Tang, Ben Zhong (Frontiers in Chemistry, 2023)
Bacterial keratitis (BK) is an acute infection of the cornea, accompanied by uneven epithelium boundaries with stromal ulceration, potentially resulting in vision loss. Topical antibiotic is the regular treatment for BK. However, the incidence rate of multidrug-resistant bacteria limits the application of traditional antibiotics. Therefore, a cationic aggregation-induced emission luminogens (AIEgens) named TTVP is utilized for the treatment of BK. TTVP showed no obvious cytotoxicity in maintaining the normal cell morphology and viability under a limited concentration, and revealed the ability to selectively combine with bacteria in normal ocular environment. After light irradiation, TTVP produced reactive oxygen species (ROS), thus exerting efficient antibacterial ability in vitro. What’s more, in rat models of Staphylococcus aureus (S.aureus) infection, the therapeutic intervention of TTVP lessens the degree of corneal opacity and inflammatory infiltration, limiting the spread of inflammation. Besides, TTVP manifested superior antibacterial efficacy than levofloxacin in acute BK, endowing its better vision salvage ability than conventional method. This research demonstrates the efficacy and advantages of TTVP as a photodynamic drug in the treatment of BK and represents its promise in clinical application of ocular infections.